(untitled) (Journal of Dhaka Medical College, 2015)
Objective: A prospective study was carried out to evaluate the role of ultrasonography in the diagnosis of hepatic metastasis and also to preoperative determination of hepatic metastasis and its validity in diagnostic process. Methods: A total of 52 patients having hepatic metastasis were enrolled in this study taken from Department of Hepatology of two tertiary level medical institutions. After sonographic evaluation of the metastatic lesion, cytopathology was done in all these patients. With written informed consent they were taken care of from the admission up to diagnosis of the hepatic metastasis, and subsequent management in hepatology unit. Place and period of study: Department of Radiology & Imaging, Department of Pathology and Department of Hepatology of Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital and of Dhaka Medical College Hospital (DMCH), during the period between July 2006 and June 2007. Results: The mean age of the patients was 51.20±11.9 years, ranging from 21 to 69 years. The highest incidence was in 60-69 years age group. The male and female ratio was 3.7:1. The most common symptom was pain with upper abdominal mass (73.1%), and others were anorexia and nausea with weight loss (67.3%), jaundice (28.8%) and ascites (23.1%). Only the right lobe of the liver was involved in 51.9% cases, left lobe in 28.8% and in 19.2% both lobes of the liver were affected. Hepatic metastasis was found as unifocal lesion in 7.7% and multifocal lesions in 92.3% cases. The echopattern was found 57.7% hyperechoic, 28.8% hypoechoic, and rest 13.5% mixed pattern. All cases were metastasis in sonography findings whereas 90.4% cases were metastasis and 9.6% other lesions in cytopathological findings. The validity of ultrasonography were determined by calculating sensitivity, specificity, accuracy, positive predictive value and negative predictive value which were 93.6%, 80.0%, 92.3%, 97.8% and 57.1% respectively. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 239-244